Uspešnost slovenske javne uprave - Rakar, Iztok (Javna uprava, 2022)
The article presents the results of the analysis of Slovenian public administration rankings on selected international comparisons in the period 2015–2020 and places them in the context of the role that transnational and international organisations have in the field of public administration development and reform. A review of the literature demonstrates that the number of international comparisons is on the rise, especially in the area of measuring performance. Based on the comparative results of selected international comparisons, we find that the Slovenian public administration has made progress on most of them. The finding are relevant for the evaluation of the achievements of the Public Administration Development Strategy 2015–2020 and is the basis for the preparation of a new strategic document in this field.
Keywords: development; international comparison; javna uprava; merjenje uspešnosti; primerjalne študije; public administration; reforme; reforms; Slovenia; Slovenija; strategy; strateški razvoj